Phylogenetics of subtribe Orchidinae s.l. (Orchidaceae; Orchidoideae) based on seven markers (plastid matK, psaB, rbcL, trnL-F, trnH-psba, and nuclear nrITS, Xdh): implications for generic delimitation. Issue 1 (December 2017) - Jin, Wei-Tao; Schuiteman, André; Chase, Mark; Li, Jian-Wu; Chung, Shih-Wen; Hsu, Tian-Chuan; Jin, Xiao-Hua
Abstract Background Subtribe Orchidinae (Orchidaceae, Orchidoideae) are a nearly cosmopolitan taxon of terrestrial orchids, comprising about 1800 species in 47 to 60 genera. Although much progress has been made in recent years of phylogenetics of Orchidinae, considerable problems remain to be addressed. Based on molecular phylogenetics, we attempt to illustrate the phylogenetic relationships and discuss generic delimitation within Orchidinae. Seven DNA markers (five plastid and two nuclear), a broad sampling of Orchidinae (400 species in 52 genera) and three methods of phylogenetic analysis (maximum likelihood, maximum parsimony and Bayesian inference) were used. Results Orchidinae s.l. are monophyletic.Satyrium is sister to the rest of Orchidinae s.l.Brachycorythis andSchizochilus are successive sister to Asian-European Orchidinae s.s.Sirindhornia andShizhenia are successive sister to clade formed byTsaiorchis -Hemipilia -Ponerorchis alliance.Stenoglottis is sister to theHabenaria-Herminium-Peristylus alliance.Habenaria, currently the largest genus in Orchidinae, is polyphyletic and split into two distant clades: one Asian-Australian and the other African–American–Asian.Diplomeris is sister toHerminium s.l. plus Asian-AustralianHabenaria . Conclusions We propose to recognize five genera in thePonerorchis alliance:Hemipilia, Ponerorchis s.l., Sirindhornia, Shizhenia andTsaiorchis . SplittingHabenaria into two genera based on morphological characters and geographical distribution may be the least disruptive approach, and it is reasonable to keepSatyrium in Orchidinae.